Risks associated with the ethical aspects of conducting clinical trials - A. L. Khokhlov; E. A. Polozova; V. A. Komissarova; N. V. Chudova; L. G. Tsyzman (Izdatelstvo OKI, 2020)
Conducting of clinical trials is closely associated with the ethical justification, with ensuring the rights and safety of the subjects participating in them. Only through trials, it becomes possible to obtain reliable data for the inclusion of new drugs in practice, which are designed to save millions of lives. In the constantly developing field of clinical research, science does not stand still and it becomes necessary to conduct more and more new research: pediatric, geriatric, biomedical products and research involving acute social problems, and of course they all involve certain risks during their implementation. The question of the ethics of conducting research in the context of the COVID-19 pandemic is very relevant at the moment, when it is necessary to make quick decisions in the interests of all mankind, assessing all possible risks that they may entail.